Design a Model in Alleviating Search Time in Large-Scale Database Retrieval - Thallapally, Adarana; Poojitha, P; Manda, Sridhar (International Journal of Computer Sciences and Engineering, 2025)
The notion of traditional public-key encryption by keyword search does not hold any hidden structure between the public-key encryption by keyword search cipher-texts; respectively, its semantic security is just defined for the keywords. We are concerned in provision of efficient search performance devoid of sacrificing semantic security within public-key encryption by keyword search. In our work we introduce searchable public-key cipher-texts by hidden structures in support of keyword search as fast as feasible devoid of sacrificing semantic security regarding encrypted keywords. Our structure is inspired by quite a lot of interesting observations based on the mechanisms of on Identity-Based Key Encapsulation. In the proposed system, the entire keyword-searchable cipher-texts that are structured by hidden relations, and by search trapdoor that corresponds to a keyword, minimum data of relations is revealed to a search algorithm as management to discover the entire matching cipher-texts resourcefully.